2006
DOI: 10.1111/j.1464-410x.2006.06320.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma magnesium and premature ejaculation: a case‐control study

Abstract: ejaculatory latency time (IELT) of < 1 min, and a control group of 19 married men with a normal IELT. All men had a history taken, a systemic physical examination and laboratory studies. After organic and psychogenic disorders were excluded, the 19 patients were included in the study. Seminal plasma and serum magnesium levels were determined using atomic absorption spectrophotometry. RESULTSThe mean ( SD ) plasma magnesium level was 94.7 (10.9) mg/L in the cases and 116.7 (11.6) mg/L in the controls. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Rosecrans et al [ 8 ] also reported that there were significant correlations of K + ( r = 0.51), carnitine ( r = 0.54), and AST ( r = 0.70) in seminal plasma and serum, but we have not observed such phenomena in present study. Other comparative studies on biochemical markers in seminal plasma and serum were focused mostly on a single marker, such as the level of Mg in seminal plasma and serum samples obtained from normal fertile men and patients with premature ejaculation [ 9 ], and the levels of Ca and Mg in seminal plasma and serum from 113 men [ 10 ]. Moreover, the levels of protein, electrolytes, enzymes, and other components in seminal plasma samples in animals such as brown bears [ 11 ], rabbits [ 12 ], stallion [ 13 ], and bactrian camels [ 14 ] have been investigated, but the useful information was very limited in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rosecrans et al [ 8 ] also reported that there were significant correlations of K + ( r = 0.51), carnitine ( r = 0.54), and AST ( r = 0.70) in seminal plasma and serum, but we have not observed such phenomena in present study. Other comparative studies on biochemical markers in seminal plasma and serum were focused mostly on a single marker, such as the level of Mg in seminal plasma and serum samples obtained from normal fertile men and patients with premature ejaculation [ 9 ], and the levels of Ca and Mg in seminal plasma and serum from 113 men [ 10 ]. Moreover, the levels of protein, electrolytes, enzymes, and other components in seminal plasma samples in animals such as brown bears [ 11 ], rabbits [ 12 ], stallion [ 13 ], and bactrian camels [ 14 ] have been investigated, but the useful information was very limited in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some small studies in patients with normal kidney function postulate a role of decreased seminal magnesium in premature ejaculation. In a case–control study by Aloosh et al,38 it was demonstrated that there was a significant relationship between seminal plasma magnesium and premature ejaculation. The same results were found in a case–control study of 38 patients by Nikoobakht et al36 However, these studies have not found any relation between serum magnesium and premature ejaculation.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased levels of magnesium result in an increase in thromboxane A2 levels, which leads to a rise in endothelial intracellular calcium and a decline in nitric oxide levels. These changes will ultimately result in cavernosal smooth muscle contraction, which might be a contributing factor to PE 100101…”
Section: Etiopathogenesis Of Pementioning
confidence: 99%